Disputed Questions in Theology and the Philosophy of Religion - Hick, John. author. aut Link
XI, 198 p.
Keywords: Deals with today's disputed religious questions - whether religious language refers to a transcendent divine reality or only reflects our own ideals, whether religious experience is a proper ground of religious belief, and whether Jesus was God incarnate or a man especially open to God's spirit.